2016
DOI: 10.1111/jfpp.12788
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Nisin on Montmorillonite: A Concentration Strategy

Abstract: The adsorption of a commercial form of nisin, Nisaplin® (Npl) (Danisco), on montmorillonite (Mt), a natural inexpensive clay mineral accepted as food additive, was assayed. The intention was to develop food grade materials capable of releasing the peptide and avoiding negative interactions that affect nisin antimicrobial activity in food environments. A set of different Mt‐Npl relation samples was prepared. The antimicrobial activity and the total organic carbon/total nitrogen (TOC/TN) content measured in nisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Nisin titer was 4,267 AU ml −1 for Mt‐NisM 0.6 sample, compared to 533 AU ml −1 for Mt‐NisM 0.24 sample (Table 2). These results are in agreement with Ibarguren, Audisio, Sham, Müller, and Farfán Torres (2017), who found a concentration effect when nisin was adsorbed from commercial samples of this bacteriocin. Furthermore, for Mt‐NisM 0.60 sample, the same thermal stability behavior as that of Mt‐NisM 0.24 was obtained (Figure S1).…”
Section: Resultssupporting
confidence: 92%
“…Nisin titer was 4,267 AU ml −1 for Mt‐NisM 0.6 sample, compared to 533 AU ml −1 for Mt‐NisM 0.24 sample (Table 2). These results are in agreement with Ibarguren, Audisio, Sham, Müller, and Farfán Torres (2017), who found a concentration effect when nisin was adsorbed from commercial samples of this bacteriocin. Furthermore, for Mt‐NisM 0.60 sample, the same thermal stability behavior as that of Mt‐NisM 0.24 was obtained (Figure S1).…”
Section: Resultssupporting
confidence: 92%
“…It indicated that a modification of the interlayer space distance occurred due to an intercalation of plantaricin Q7 in montmorillonite layers, suggesting that plantaricin Q7 probably adsorbed on montmorillonite by 'frustrated intercalation' . These results are in agreement with Ibarguren [8,25]. TEM micrographs of montmorillonite and plantaricin Q7 adsorbed montmorillonite are shown in Fig.…”
Section: Characterization Of Plantaricin Q7 Adsorbed On Montmorillonitesupporting
confidence: 91%